PENGARUH PEMBERIAN EKSTRAK DAUN KENIKIR (Cosmos caudatus Kunth) TERHADAP KADAR MALONDIALDEHYDE PADA TIKUS PUTIH GALUR WISTAR DIABETIK - Rizky Dermawan (2022)
Diabetes Mellitus (DM) is a chronic disease with a high prevalence and continues to increase every year. High level production of free radicals in DM trigger lipid peroxidation to form Malondialdehyde (MDA) and cause cell damage and complications, so it needs to be treated. Kenikir leaves (Cosmos caudatus Kunth) have the potential to be used as antihyperglycemic and antioxidant. This study was conducted to determine the effect of giving kenikir leaf extract to the levels of Malondialdehyde (MDA) of diabetic Wistar rats. This research is a true experimental with post test only control group design. 30 samples of White male wistar rats, aged 2-3 months, weighing 150-200 g, are divided into 6 groups. Group 1 was given standard feed and drink (Normal Control), group 2 was given alloxan 125 mg/kgBW (Negative Control), Group 3 was given alloxan and metformin 500 mg/kgBW (Positive Control), Groups 4, 5, and 6 were given alloxan and kenikir leaf extract (150, 300, and 600) mg/kgBW. The treatment was given for 14 days, followed by MDA levels examination with the TBARS test using a spectrophotometry at 532 nm. The results of the One Way ANOVA test showed that there was an effect of giving kenikir leaf extract on MDA levels (p = 0.000). The results of Bonferroni test stated that kenikir leaf extract at a dose of 600 mg/kgBW was the most effective dose in reducing MDA levels about normal values (p = 1,000).